Retrospective analysis of disease association and outcome in histologically confirmed ischemic colitis. Issue 5 (15th April 2013) - Mosli, Mahmoud; Parfitt, Jeremy; Gregor, Jamie
<x xml:space="preserve">Abstract</x> Objective To identify risk factors, clinical features and complications in patients with ischemic colitis (IC). Methods All patients diagnosed with biopsy proven IC within a 2‐year period were identified; clinical data were retrospectively collected and subsequently analyzed. Results In total, 72 IC patients with a mean age of 68 years were included in this study. Among them, 18 (25.0%) were younger than 65 years with a female predominance. One‐third of the patients was found to be without vascular risk factors, and 8 patients met the criteria for irritable bowel syndrome. No history of oral contraceptives or hormonal replacement therapy use could be found among the women diagnosed with IC. Over a mean duration of follow‐up of 9.5 months (range 0–65 months), the rate of recurrent disease was 16.7%, while only 2 (2.8%) patients developed extra intestinal vascular sequelae. Statistical analysis identified a history of atrial fibrillation and the use of furosemide to be the only significant predictors of a poor outcome, while coronary artery disease and chronic renal failure predicted recurrence and low platelet count predicted stricture formation. Conclusions Although most patients with IC are elderly and have conventional vascular risk factors, it should also be considered in young patients without vascular risk factors, especially in women, who may have an atypical distribution of the disease. Severe complications and extraintestinal vascular sequelae are rare, however, residual gastrointestinal complaints and recurrent disease are relatively common and there are no reliable predictors of the outcome.